Stability of an n-Dimensional Mixed-Type Additive and Quadratic Functional Equation in Random Normed Spaces - Yang-Hi Lee; Soon-Mo Jung (Journal of Applied Mathematics)
We investigate the stability problems for the n-dimensional mixed-type additive and quadratic functional equation 2f(∑j=1nxj)+∑1≤i,j≤n,  i≠jf(xi-xj)=(n+1)∑j=1nf(xj)+(n-1)∑j=1nf(-xj) in random normed spaces by applying the fixed point method.